Comparison of motor competence in children aged 6 to 9 years across northern, central, and southern European regions - Laukkanen, Arto (2019)
The present study aimed at examining differences in motor competence (MC) in children aged 6 to 9 years old in northern, central, and southern European regions using the Körperkoordinationstest für Kinder (KTK). The secondary aim of the study was to examine interactions between region and children's age, sex and weight status (determined as healthy weight or overweight/obese). Data was pooled from independent studies conducted in Finland (mean age 7.81 ± 1.19 years, n = 690), Belgium (mean age 8.25 ± 1.09 years, n = 1,896) and Portugal (mean age 8.31 ± 1.02 years, n = 758) between 2008 and 2016. Cross-cultural differences in MC and interaction effects were tested using ANOVAs and ANCOVAs. Age, sex and BMI percentile were used as covariates. Geographical region significantly explained 19% of the variance in MC, while BMI (5%), sex (3%) and age (0.3%) were significant covariates. The interaction effect of region and age (5%), region and sex (0.6%) and region and BMI (0.2%) on MC was also significant. Cross-cultural differences in children's MC seem to increase substantially across 6 to 9 years, independent of the prevalence of overweight or obesity. Girls slightly underperformed in MC compared to boys in regions where the overall level of MC was lower. On the other hand, the association between body weight status and MC seems relatively consistent across the cultures. Future cross-cultural studies should further explore the influence of individual (e.g. physical activity) and environmental (e.g. physical activity and sport policy) factors on MC development.